Theory and practice of model transformations : 6th International Conference, ICMT 2013, Budapest, Hungary, June 18-19, 2013. Proceedings - Kappel, Gerti; Duddy, Keith (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 6th International Conference on Theory and Practice of Model Transformations, ICMT 2013, held in Budapest, Hungary, in June 2013. The 13 full papers and 5 tool and application demonstrations were carefully selected from 58 submissions. The papers are grouped in topical sections which focus on new programming models, tools and applications, evolution and synchronization, transformation engineering, and testing.